2017
DOI: 10.1016/j.saa.2016.10.041
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of postmortem biochemical changes in rabbit plasma using ATR-FTIR combined with chemometrics: A preliminary study

Abstract: Postmortem interval (PMI) determination is one of the most challenging tasks in forensic medicine due to a lack of accurate and reliable methods. It is especially difficult for late PMI determination. Although many attempts with various types of body fluids based on chemical methods have been made to solve this problem, few investigations are focused on blood samples. In this study, we employed an attenuated total reflection (ATR)-Fourier transform infrared (FTIR) technique coupled with principle component ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 36 publications
(16 citation statements)
references
References 51 publications
0
15
0
1
Order By: Relevance
“…In the present study, the PLS model was established based on the calibration dataset and used to predict validation samples. Numerous studies have confirmed the efficiency of this supervised model in classifying or predicting different categories of biological tissues [ 41 , 42 , 14 ]. In Figure 5 A, the PLS score plot illustrates a straightforward separation amongst the four groups, where the control, 12, and 24h groups were distributed along LV1 accounting for 53.72% of total variance, while 24 h and the remaining groups were segregated along LV2 (18.90% of total variation).…”
Section: Resultsmentioning
confidence: 84%
See 1 more Smart Citation
“…In the present study, the PLS model was established based on the calibration dataset and used to predict validation samples. Numerous studies have confirmed the efficiency of this supervised model in classifying or predicting different categories of biological tissues [ 41 , 42 , 14 ]. In Figure 5 A, the PLS score plot illustrates a straightforward separation amongst the four groups, where the control, 12, and 24h groups were distributed along LV1 accounting for 53.72% of total variance, while 24 h and the remaining groups were segregated along LV2 (18.90% of total variation).…”
Section: Resultsmentioning
confidence: 84%
“…Emerging evidence shows its great potential as a new promising diagnostic method to detect chemical changes from multiple macromolecules including proteins, lipids, carbohydrates, and nucleic acids, in biological tissues [ 12 , 13 ]. Combination with IR microscopy allows for spectral collection in complex and heterogeneous tissues with minimal sample preparation, and the acquired spectral fingerprints can yield subsequent classification of spectra into different categories using objective computational algorithms [ 14 , 15 ]. According to its numerous advantages, this spectroscopic technique has been widely used in various murine brain models, including ischemic brain injury [ 16 ], Alzheimer’s disease [ 17 ], brain tumors [ 18 ], and multiple sclerosis [ 19 ], but only a few attempts have been made to study TAI [ 20 – 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, this promote us to develop a FTIR-based method for auxiliary diagnosis in cases of electrocution, which could provide a more objective and intuitive identification of electrical mark than routine histological examination. In this study, the PLS model was chosen to process the spectral dataset because it has been demonstrated that this supervised pattern recognition method is powerful for distinguishing different sample categories[2528]. The spectra in the calibration group were used to establish the initial PLS model.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, FTIR has been used for the analysis, detection and identification of body fluids and biological tissues [14,15]. In our previous work, satisfactory results were achieved using attenuated total reflection-FTIR (ATR-FTIR) for the analysis of time-dependent changes in biological tissues, combining with chemometric methods which further improved the accuracy of the results [16][17][18][19][20]. In the field of semen research, FTIR has been used to characterize human sperm in clinical settings [21].…”
Section: Introductionmentioning
confidence: 99%